2010
DOI: 10.4236/psych.2010.13029
|View full text |Cite
|
Sign up to set email alerts
|

Middle Ear Effusion, Attention, and the Development of Child Behavior Problems

Abstract: Objective: Much interest centers on whether middle ear effusion (MEE) early in life has lasting developmental consequences. It was hypothesized that episodic loss of hearing acuity associated with MEE results in a deficit in attention, a core factor in the development of child behavior problems, and that impaired attention is related to behavior problems during the early years of childhood. Method: This was a prospective study of a large sample of children (n = 698) that was representative of the local populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…Regarding OME, a large longitudinal cohort study with the Child Behavior Checklist in a group of children found no association between hearing loss and behavioral problems. 41 This was also reported by Minter et al 43 However, a large cohort study with a similar level of evidence used Rutter’s Behavior Scale and the Connors’ Hyperactivity Index and found an association between OME and hyperactive, antisocial, and neurotic behavior. 42 This study was significantly limited by a crude assessment of OME through subjective parental report of suspected/confirmed hearing loss and purulent ear drainage.…”
Section: Resultssupporting
confidence: 63%
See 3 more Smart Citations
“…Regarding OME, a large longitudinal cohort study with the Child Behavior Checklist in a group of children found no association between hearing loss and behavioral problems. 41 This was also reported by Minter et al 43 However, a large cohort study with a similar level of evidence used Rutter’s Behavior Scale and the Connors’ Hyperactivity Index and found an association between OME and hyperactive, antisocial, and neurotic behavior. 42 This study was significantly limited by a crude assessment of OME through subjective parental report of suspected/confirmed hearing loss and purulent ear drainage.…”
Section: Resultssupporting
confidence: 63%
“…[28][29][30][31][32][33][34][35][36][37][38][39][40] Eight studies assessed behavior among DHH children who had otitis media with effusion (OME) or minimal/unilateral hearing loss ( Table 3). [41][42][43][44][45][46][47][48] Of the 36 articles, 2 studies also explored interventional methods for this population. 49,50 The included studies occurred from 1985 to 2015 and took place in the United States, Taiwan, New Zealand, Australia, Spain, India, the United Kingdom, Turkey, the Netherlands, Germany, and Canada.…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, all the participants in our experimental group reported a history of recurrent otitis media. While the data does not speak directly to any definitive links with OME, it may be that due to the transient disruptions in hearing associated with recurrent OME3940 the experimental group may have learnt to allocate most of their cognitive resources to selectively focus attention on expected information and the remaining resources are insufficient for them to switch their attention to any unexpected stimulus. Future studies are needed to evaluate this hypothesis.…”
Section: Discussionmentioning
confidence: 75%